Assimilating construction worker safety into design – a review - Che Ahmad, Asmalia; Bahari, Ismail (2008)

(untitled)
Construction industry is an essential element in Malaysian economy. However, with the highest fatality rate compared to other industries in the country, construction industry faces a great challenge. In order to address this challenge, researches have demonstrated that decisions made throughout construction upstream activity i.e. the design stage can stimulate construction safety. In Malaysia, safety topics are often not highlighted until the start of construction stage. Assimilating construction worker safety in the design consideration presents designs that are safe to be built and maintain. During design process, designers can provide best safety practices such as modification to permanent features, preparation of plans and specifications with construction safety is considered. Besides, communication of risk regarding design and utilization of specific safe design can also be integrated to eliminate or reduce hazards during construction and occupational stage. Assimilating construction worker safety into design is consistent with safety hierarchy of control which calls for eliminating or minimizing hazard before relying on management or temporary controls to protect workers. This paper aims to review the concept of assimilating construction worker safety into design published by various literatures.